BRICS: AN OPTION TO THE WORLD BANK AND THE IMF - Ahmad Bhat, Mukhtar; Ahmad Shah, Mubashir (International Journal of Psychosocial Rehabilitation, 2019)
The purpose of this paper is to evaluate and study the objective, functions and the role of Brazil, Russia, India, China, South Africa (BRICS) New Development Bank as a financial institution. This paper will also analyse whether BRICS has the potential to be an alternative to the World Bank and International Monetary Fund (IMF), destabilizing the current development finance framework. More importantly, if the BRICS Bank project succeeds, what are the possible scenarios for the field of development cooperation? All countries in the world have their own national interests. BRICS members too have their national interests and they have realized that BRICS Bank is a useful idea for advancing those interests. As BRICS is a combination of diverse geographical and cultural backgrounds, it will be imperative to know how these diverse countries cooperate in a world which is largely dominated by the USA and its influence on two financial institutions namely World Bank and IMF.